Japanese medicinal drug labeling for use in the clinical setting as informed by pharmacogenomic data on cytochrome P450 enzymes obtained from in silico studies - Tanaka, Yoichi; Shimizu, Makiko; Saito, Yoshiro; Yamazaki, Hiroshi (Drug metabolism and pharmacokinetics, 2025)
Although the United States Food and Drug Administration has disclosed a list of drugs with pharmacogenomic biomarkers for drug labeling, there is limited information regarding pharmacogenomic-associated drugs in Japan. Such associations include genetic variants of uridine diphosphate glucuronosyltransferase 1A1 for irinotecan, nudix hydrolase 15 for thiopurine drugs, and cytochrome P450 (P450) 2C9 for siponimod. The effects of such genetic variants on drug concentrations are similar to those from drug interactions. Because of race and dosage differences, the relevance of pharmacogenomic associations in Asian populations requires confirmation. This white paper proposes that in vitro pharmacogenomic information can be used to predict human pharmacokinetics and to describe in drug labels the changes in blood concentrations by genetic variants. For P450 variants CYP2C9∗3, CYP2C19∗2, CYP2C19∗3, CYP2D6∗10, and CYP3A4∗16, we propose using the enzymatic activity parameters obtained from in vitro functional analysis of the drug-metabolizing enzymes for multiple substrate drugs to predict the effects of these variants on human pharmacokinetics. Consequently, in patients prescribed only a single drug, anything more than a “moderate effect” on plasma exposure should be mentioned as a caution in the drug labels; such effects are likely caused by enzyme polymorphisms resulting in similar effects to drug–drug interactions. [Display omitted]